Management of Open Fractures in Low-Income Countries: a Daunting Task - Jean Baptiste Ramampisendrahova; Mamisoa Bodohasina Rasamoelina; Tsiahoana Jean Floris Tata; Rado Razafimahatratra; Gaëtan Duval Solofomalala (Journal La Medihealtico, 2021)
Abstract The management of open fractures was a challenge from antiquity to the present day. The objective of this study is to report the difficulties of the management of open fractures of long bones in low-income countries. This was a retrospective cohort study of the files of patients admitted for open fracture of long bones in the Department of Orthopedic Surgery and Traumatology of the Anosiala University Hospital Center for four years. Forty-two open long bone fractures were collected. The average age of the patients was 36.3 years of which 73.8% were subject of working age in the age group of 20 to 60 years and 73.8% of the cases were following the accident of the road. Most of the wounded had arrived at the hospital by bush taxi. The tibia was the most affected bone (71.4%). Gustilo IIIA type open fractures were the most observed (38.1%). Only 26.3% of patients had received surgical debridement before the sixth hour. 76.2% had no care before arriving at the hospital, 14.3% had emergency care at the basic health center and 9.5% were already being treated by the traditional healer. Definitive treatment of the fracture was dominated by the external fixator (38.1%) and orthopedic treatment (26.2%). In low-income countries, the management of open fractures remains a daunting task. The main factors limiting the management of open fractures were the poverty of the population, the lack of health insurance coverage and the retard in arriving at the hospital. Keywords: open fractures, management, low-income, country